Міри внутрішньої та зовнішньої інформації (на прикладі ймовірнісних ситуацій невизначеності). - Diduk, N. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2014)
It is shown that external information, causing transformations of situations of uncertainty, can enter by information channels. This occurs in two stages. First the very existence of the channel creates external information, which causes induction of the situation of uncertainty on the channel output and creates information relationship between the two systems. Hereon becomes possible operation of created information relationship. The material aspect of the operation is reduced to production of the signal at the channel input and following its transmission through the channel. Information aspect consists in the following. Each event of the appearance of the signal at the input or output of the channel creates external information, which leads to compelled change of the situation of uncertainty on the opposite end of the channel. Three transformations of information, connected with information channel, were subjected to study: induction of the situation of uncertainty on the channel output, creation of information relationship between two systems and forcing of the situation of uncertainty on the channel output. It is received evidence that internal information can be transformed in external information. Conclusions from the article are formulated.